Safety and efficacy of prophylactic levetiracetam for prevention of epileptic seizures in the acute phase of intracerebral haemorrhage (PEACH): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 9 (September 2022) - Peter-Derex, Laure; Philippeau, Frédéric; Garnier, Pierre; André-Obadia, Nathalie; Boulogne, Sébastien; Catenoix, Hélène; Convers, Philippe; Mazzola, Laure; Gouttard, Michel; Esteban, Maud; Fontaine, Julia; Mechtouff, Laura; et al.
Summary: Background: The incidence of early seizures (occurring within 7 days of stroke onset) after intracerebral haemorrhage reaches 30% when subclinical seizures are diagnosed by continuous EEG. Early seizures might be associated with haematoma expansion and worse neurological outcomes. Current guidelines do not recommend prophylactic antiseizure treatment in this setting. We aimed to assess whether prophylactic levetiracetam would reduce the risk of acute seizures in patients with intracerebral haemorrhage. Methods: The double-blind, randomised, placebo-controlled, phase 3 PEACH trial was conducted at three stroke units in France. Patients (aged 18 years or older) who presented with a non-traumatic intracerebral haemorrhage within 24 h after onset were randomly assigned (1:1) to levetiracetam (intravenous 500 mg every 12 h) or matching placebo. Randomisation was done with a web-based system and stratified by centre and National Institutes of Health Stroke Scale (NIHSS) score at baseline. Treatment was continued for 6 weeks. Continuous EEG was started within 24 h after inclusion and recorded over 48 h. The primary endpoint was the occurrence of at least one clinical seizure within 72 h of inclusion or at least one electrographic seizure recorded on continuous EEG, analysed in the modified intention-to-treat population, which comprised all patients who were randomly assigned to treatment and who had a continuous EEG performed. This trial was registered at ClinicalTrials.gov, NCT02631759, and is now closed. Recruitment was prematurely stopped after 48% of the recruitment target was reached due to a low recruitment rate and cessation of funding. Findings: Between June 1, 2017, and April 14, 2020, 50 patients with mild-to-moderate severity intracerebral haemorrhage were included: 24 were assigned to levetiracetam and 26 to placebo. During the first 72 h, a clinical or electrographic seizure was observed in three (16%) of 19 patients in the levetiracetam group versus ten (43%) of 23 patients in the placebo group (odds ratio 0·16, 95% CI 0·03–0·94, p=0·043). All seizures in the first 72 h were electrographic seizures only. No difference in depression or anxiety reporting was observed between the groups at 1 month or 3 months. Depression was recorded in three (13%) patients who received levetiracetam versus four (15%) patients who received placebo, and anxiety was reported for two (8%) patients versus one (4%) patient. The most common treatment-emergent adverse events in the levetiracetam group versus the placebo group were headache (nine [39%] vs six [24%]), pain (three [13%] vs ten [40%]), and falls (seven [30%] vs four [16%]). The most frequent serious adverse events were neurological deterioration due to the intracerebral haemorrhage (one [4%] vs four [16%]) and severe pneumonia (two [9%] vs two [8%]). No treatment-related death was reported in either group. Interpretation: Levetiracetam might be effective in preventing acute seizures in intracerebral haemorrhage. Larger studies are needed to determine whether seizure prophylaxis improves functional outcome in patients with intracerebral haemorrhage. Funding: French Ministry of Health.